Myeloid-specific deficiency of pregnane X receptor decreases atherosclerosis in LDL receptor-deficient mice[S] - Yipeng Sui; Zhaojie Meng; Se-Hyung Park; Weiwei Lu; Christopher Livelo; Qi Chen; Tong Zhou; Changcheng Zhou (Journal of Lipid Research, 2020)
The pregnane X receptor (PXR) is a nuclear receptor that can be activated by numerous drugs and xenobiotic chemicals. PXR thereby functions as a xenobiotic sensor to coordinately regulate host responses to xenobiotics by transcriptionally regulating many genes involved in xenobiotic metabolism. We have previously reported that PXR has pro-atherogenic effects in animal models, but how PXR contributes to atherosclerosis development in different tissues or cell types remains elusive. In this study, we generated an LDL receptor-deficient mouse model with myeloid-specific PXR deficiency (PXRΔMyeLDLR−/−) to elucidate the role of macrophage PXR signaling in atherogenesis. The myeloid PXR deficiency did not affect metabolic phenotypes and plasma lipid profiles, but PXRΔMyeLDLR−/− mice had significantly decreased atherosclerosis at both aortic root and brachiocephalic arteries compared with control littermates. Interestingly, the PXR deletion did not affect macrophage adhesion and migration properties, but reduced lipid accumulation and foam cell formation in the macrophages. PXR deficiency also led to decreased expression of the scavenger receptor CD36 and impaired lipid uptake in macrophages of the PXRΔMyeLDLR−/− mice. Further, RNA-Seq analysis indicated that treatment with a prototypical PXR ligand affects the expression of many atherosclerosis-related genes in macrophages in vitro. These findings reveal a pivotal role of myeloid PXR signaling in atherosclerosis development and suggest that PXR may be a potential therapeutic target in atherosclerosis management.